Transdermal permeation of curcumin promoted by choline geranate ionic liquid: Potential for the treatment of skin diseases - Rodrigo Boscariol; José M. Oliveira Junior; Denicezar A. Baldo; Victor M. Balcão; Marta M.D.C. Vila (Elsevier, 2022)
The transdermal permeation of curcumin aided by choline and geranic acid ionic liquid (CAGE-IL) was addressed as a potential treatment for skin diseases. An in-depth analysis of the effect of CAGE-IL concentration in the enhancement of transdermal permeation of curcumin was performed, and the results were modelled via nonlinear regression analysis. The results obtained showed that a low percentage of CAGE-IL (viz. 2.0%, w/w) was effective in disrupting the skin structure in a transient fashion, facilitating the passage of curcumin dissolved in it.